Religious Moderation in Indonesia: Navigating Conflict and Pluralism through Agonistic Democracy - Danisworo, Tunggul Ganggas; Rahmatunissa, Mudiyati; Paskarina, Caroline (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2024)
Indonesia's religious diversity presents significant challenges, particularly in managing public expressions of religious identity and achieving equality in diversity. To address these issues, the government introduced a religious moderation policy in 2019, which aims to foster tolerance and manage the relationship between religion and the state. This policy, formalized through Presidential Regulation No. 58 of 2023, aims to create a tolerant society that values diversity. However, the policy has faced criticism for emphasizing harmony over religious freedom and potentially favoring the majority religion, thus risking repressive pluralism and government control over religious practices. This study critically analyzes the religious moderation policy using the perspective of agonistic pluralism, which emphasizes the importance of conflict and diversity in democratic life. Using qualitative methods and Ernesto Laclau's critical discourse analysis, this study explores the policy's ability to redirect conflict constructively and prevent hegemonic domination. The findings show that while the policy aims to harmonize religious diversity, it risks undermining pluralism by imposing a state-supported version of religious practice, potentially sidelining minority religions and indigenous faiths. The conclusion is that the government's approach to articulating a discourse of moderation has the potential to create a kind of harmony that appears on the surface but is not authentic. By integrating values such as tolerance and anti-extremism into the dominant narrative, the government seeks to homogenize religious practice and eliminate legitimate diversity of views, which can ultimately curb the dynamics of healthy pluralism and create a false harmony that benefits certain power agendas.